Case study: Lead time management in furniture manufacturing / Wan Fadlina Wan Chik Ahmad and Norhafizah Rosman - Wan Chik Ahmad, Wan Fadlina; Rosman, Norhafizah (2011)
Lead time management is needed in most activity to get the good quality of the product and management. Lead time is the amount of time between the placing of an order and the receipt of the goods ordered. Time in the organization is constant and irreversible. TIRAI INNOVATIF Sdn.Bhd. was chosen for this experiment becquse the important of the successful of the company depends on timing of the company finish their product. It will keep their reputation that can finish their work on time. In measuring time the method that use is stopwatch that can record time workers work and get the result refer to the time record. The timing that was taking was the result that needed to discuss and to know the effectiveness labor to finish the product and the efficiency of labor refers to the product. Nothing can be substituted for time. Worse, once wasted, it can never be regained. Efficiency and effectiveness of labor is important to help company to produce output on time.